Mastering advanced modern Chinese through the classics an advanced language and culture course - Wu, Shu-Ling; Yuan, Haiwang (Routledge, 2019)
"Mastering Advanced Modern Chinese through the Classics is a textbook to teach those who wish to achieve an advanced or native proficiency and cultural competence in modern Chinese, as well as to experience the beauty of classical Chinese literature. Collecting representative works containing vibrant views of Chinese culture from different dynasties, this book is focused on how the grammatical patterns, vocabulary, and idioms that are found in classical Chinese are relevant in the modern adaptation of the language, and how the accumulated traditional values and beliefs found there still shape the thinking and lifestyle of modern society. Online resources including audio, answer keys and instructor aids will be part of the teaching package"--